Medical Features, Clinical Investigative Findings, Hormonal Parameters and Husband’s Semen Analysis in Infertile Women Attending Outpatient Departments of Obstetrics and Gynecology at Two Hospitals in Dhaka City Bangladesh - Giasuddin, Abu Sayed Mohammad; Parveen, Neaz T.; Banu, Laila Arjumand; Parveen, Shohela (British Journal of Healthcare and Medical Research, 2025)
Background: Women infertility is a multifactorial issue with social, economic and cultural influence and it is a global health problem; Objectives: The study was conducted to determine types of infertility and their contributing factors among infertile women at Dhaka city, Bangladesh; Methodology: This prospective cross-sectional study was conducted among infertile women attending two Outpatient Departments (OPDs) of Gynecology & Obstetrics at Impulse Hospital, Tejgaon, Dhaka, Bangladesh and Popular Hospital Ltd., Mirpur, Dhaka, Bangladesh from December 2024 to March 2025. A total of 130 infertile women (Age: 18-40 Years) were included in the study from December 2024 to March 2025 with proper investigations and evaluation for types of infertility and their contributing factors. Data were collected using a semi-structured information collection sheet by face-to-face interviewing followed by relevant clinical and Laboratory investigations. The data were analysed statistically and reported accordingly; Results: Out of 130 infertile women, primary infertility was found among 73 (56.2%) and secondary infertility was found among 57 (43.8%) of respondents. Regarding body mass index (BMI), majority of the respondents had normal (56,43.1%) followed by overweight (46, 35.4%), obese (17,13.1%) and thin (11,8.4%) BMI. Large proportions of infertile women from both primary and secondary categories of infertility had BMI in the overweight and obese ranges. Psychological features such as anxiety and depression were not significantly present in both categories of infertility. Transvaginal (TV) scanning revealed that overall, 61 (46.9%) had normal ovary with 30 (23.1%) had fibroids and 39 (30.1%) had polycystic ovarian syndrome (PCOS). TV scan findings were not significantly different between the women with primary and secondary infertility. Serum prolactin levels (127, 97.6%) and TSH levels (120, 92.3%) were within normal ranges. Semen analyses of husbands showed mostly normal pattern (104, 79.9%); Conclusions: TV scanning findings should be meticulously evaluated, interpreted and used for establishing the women infertility accordingly. The studies with larger samples, longer duration and multicentered evaluating psychological features and molecular genetic factors also are recommended to assess the accurate picture of women infertility and its causes in Bangladesh. Women infertility should be treated as a significant national public health issue and government should develop effective policy to help these women and mitigate the problem.